Genetic Resources: The Base Material for Managing Nature - Pastorino, Mario Juan; Marchelli, Paula (Elsevier, 2022)
Genetic resources from any biological organism-complete genomes, genes, or even portions of genes that have actual or potential relevance to humans—are a provisioning ecosystem service. They are essential to ensure the resilience and persistence of ecosystems and the process of evolution, and in this sense, conserving them is an ethical duty. Moreover, they are crucial to domesticate or improve species used in the production of food, fiber and drugs, and in many other processes for the benefit of humankind. On the other hand, genetic resources are threatened by natural and human-induced factors, which can be gradual (e.g., climate change) or sudden (e.g., fire). Overexploitation, land use change, alien species invasion, pollution, and fragmentation are among the main drivers of genetic resource loss. Genetic resources can be conserved either in situ (in natural ecosystems) or ex situ (in artificial environments). Seed banks are the most widespread ex situ conservation strategy, but alternatives such as pollen banks, in vitro conservation, cryopreservation, DNA storage, microorganism culture collections, and field gene banks are also used. Genetic markers and common garden trials are the proper tools to characterize and evaluate genetic resources.